Rationality of Tuberculosis Treatment for Drug-Susceptible Pulmonary Tuberculosis at a Primary Care in Bandung - Islamiyah, Alfi Nurul; Syarifuddin, Syarifuddin; Akhsa, Morsalina; Rukmawati, Iis; Margayani, Eni; Suherman, Linda Purnamawati; Septiani, Vina; Ramdani, Robby (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Tuberculosis (TB) remains a significant global health concern, particularly in Indonesia. Ensuring rational TB treatment is crucial for effective disease control and preventing the emergence of drug resistance. This study aimed to evaluate the rationality of TB treatment among newly diagnosed drug-susceptible pulmonary TB patients in a primary care center in Bandung. A descriptive-analytical study was conducted on 56 patients who met the inclusion and exclusion criteria. Treatment rationality was assessed based on the Indonesian Society of Respirology 2021 and the National Guidelines for Medical Services 2020. While 100% of patients received the correct medication for the right indication and dose, the duration of therapy was suboptimal for most patients (83.93%) due to drug unavailability. This resulted in a lower-than-ideal treatment regimen, potentially compromising treatment outcomes and increasing the risk of drug resistance. These findings highlight the need for improved drug supply management and adherence to treatment guidelines to optimize TB treatment outcomes and reduce the burden of TB in Indonesia.